Assessment of biomass burning and fossil fuel contribution to black carbon concentrations in Delhi during winter. (December 2018) - Dumka, U.C.; Kaskaoutis, D.G.; Tiwari, S.; Safai, P.D.; Attri, S.D.; Soni, V.K.; Singh, N.; Mihalopoulos, N.
Abstract: This study aims to assess the contribution of fossil-fuel combustion (BCff ) and biomass (or wood) burning (BCwb ) to wintertime black carbon (BC) concentrations in Delhi using the "Aethalometer model" approach. Continuous measurements using 7-wavelength Aethalometer (AE-33) were taken from December 2015 to February 2016 in Delhi downtown, as part of a multi-instrument research campaign, revealing high BC concentrations of 24.4 ± 12.2 μg m −3 (range from 3.2 to 59.9 μg m −3 ). The BCff contribution dominates with an average fraction of 72% at 880 nm, indicating an important contribution from biomass burning (28%). The daily-averaged Absorption Ångström Exponent (AAE370-880 ) varies between 1.08 and 1.46 due to changes in the BC emission rates, variations in the relative strength between fossil-fuel and wood-burning sources and mixing processes in the atmosphere. The average BCff /BCwb ratio is estimated as 2.90 ± 1.47 at 880 nm, while the BCwb contribution maximized in the evening hours due to enhanced wood burning for heating. The BC, BCff and BCwb concentrations exhibit remarkable diurnal variations with maximum values in the morning and evening/night hours and lower around noon, primarily driven by changes in the mixing-layer height. The highest BC, BCff and BCwb concentrations are associated with weak winds (<2 ms −1 ), revealing a dominance of local emission sources within the Delhi metropolitan area. A sensitivity analysis is performed by changing the wavelength pairs and the pre-assumed AAE values in order to evaluate the stability of the "Aethalometer model" in assessment of the BC source apportionment. The results reveal that the "Aethalometer model" is more sensitive in estimating the BCwb, while the changes in the BCff component are rather low. Graphical abstract: Highlights: Daily-mean BC concentrations range from 3.2 to 59.9 μg m −3 in Delhi during winter. The BCff vs BCwb estimations are 72% vs 28% at 880 nm. Dependence of BCff and BCwb on AAEff and AAEwb values (Aethalometer model). Higher BCff /BC during early morning, higher BCwb /BC in the evening. Boundary-layer dynamics control the BC concentrations.